Formulasi untuk Memperbaiki Flovor Bubur Buah Alpukat (Persea americana Mill) Hasil Restrukturisasi - Zaki Utama; Sri Raharjo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2006)
The objective of this experiment was to develop novel restructured products from fresh avocado fruits puree and calcium-alginate gel forming method (internal setting). Gel forming by internal setting the calcium is released under controlled conditions simultaneously throughout the system. Restructuredfruit products were evaluated for pH, color, and sensory properties. Sodium chloride (0.5% and 1.0%) did not give better flavor for restructured avocado compare to product without it. The addition of sodium chloride precisely increases the sourness of the product. Restructured avocado product with citric acid concentration 0.05% and 0.1% were much preferred than product with citric acid concentration 0.5%. The addition of sugar (5%) to the restructured product significantly reduced the sourness. Compared to the addition of sodium chloride (0.5%), products with addition of sugar (2.5% and 5%) were significantly more preferable and the flavors were closer to fresh-cut avocado fruit.